Contemporary Perspectives on Social Work in Acquired Brain Injury: An Introduction. Issue 3 (12th December 2016) - Simpson, Grahame; Yuen, Francis
ABSTRACT: This special issue of the Journal of Social Work in Disability and Rehabilitation, "Contemporary Perspectives on Social Work in Acquired Brain Injury, " has been initiated and coordinated by the International Network of Social Workers in Acquired Brain Injury (INSWABI). In introducing the issue, some space is allocated for providing definitions of traumatic brain injury (TBI) and acquired brain injury (ABI), outlining the epidemiology and global costs, and detailing the impairments and psychosocial impacts for both the person sustaining the injury and his or her family. Finally, an outline of the articles contributing to this special issue are detailed, followed by a brief discussion about the role of the INSWABI network in promoting best practice in social work within this specialty area.